IB Hijrah KPR Financing Mechanism with Murabahah Akad at Bank Muamalat - Olga Mutiara Umi; Romi Adetio Setiawan; Syaifudin Syaifudin; Andika Eko Prasetiyo (Yayasan Darussalam Bengkulu, 2024)
This research aims to comprehend the mechanism of financing for Islamic Home Ownership Credit (Kredit Pemilikan Rumah - KPR), particularly KPR IB Hijrah, and seeks solutions to address financing issues arising through the application of the murabahah contract at Bank Muamalat Bengkulu Kc S. Parman. The research method employed is field research with a qualitative descriptive approach. Data were gathered through observation, interviews, and documentation. The study concludes that the KPR IB Hijrah financing process involves stages such as application submission, fulfillment of requirements, scrutiny of document prerequisites, financing approval, and the execution of the murabahah contract. Customer responses to the financing mechanism indicate a clear understanding of requirements and administrative costs. To address emerging financing problems, the researcher recommends several solutions. Firstly, a direct approach to customers to provide a deeper understanding of the issues they face. Secondly, proactive and periodic debt collection efforts to prevent payment delinquencies. Additionally, issuing warning letters can serve as an initial step in resolving issues. In more complex cases, restructuring of financing is suggested as an alternative solution. Finally, if necessary, collateral execution can be implemented as a last resort in resolving problematic financing.